The Effect of Occupational Supervision and Discipline on Employee Performance in the National and Political Unity Agency of Seluma District - Levi Bastian; Sulisti Afriani; Yanto Effendi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this study was to determine the effect of supervision and work discipline on the performance of the State Civil Apparatus at the National Unity and Political Body of Seluma Regency. The sample in this study were 32 employees at the Seluma Regency Political and National Unity Agency. Data collection using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results of multiple linear regression calculations obtained the multiple linear regression equation Y = 9.019 + 0.425X1 + 0.379X2 + 6.272 (e). The coefficient of determination of the Adjusted R square value is 0.473. This means that X1 (supervision), X2 (work discipline have an effect on performance (Y) by 47.3% while the remaining 52.7% is influenced by other variables that are not researched. in this research. The results of the F test indicate that the significance is 0.000 <0.05. Because the significance level is below 0.05, it indicates that together X1 (supervision) and X2 (work discipline) have a positive and significant effect simultaneously on performance (Y). Supervision has a positive and significant effect on performance because the significant value is 0.014 <0.05, work discipline has a positive and significant effect on performance because the value is 0.035 <0.05.